Producción del curso virtual sobre el uso del software “OpenSim” como herramienta de apoyo didáctico - López Falcón, Gerardo (2014)
This article stands from a research project entitled Production of a virtual course on using the OpenSim software as a tool for teaching support, conducted during 2012-2013 in the Master Program of Educational Technology and Computing, at UNA, providing training to integrate new technology to present the academic population a new set of tools, the potential of new learning environments in three dimensions and thus collaborate with the function that the Virtual Program has to investigate and analyze the pedagogical potential of different technological tools to develop proposals that benefit both the teaching community and the student population. The course design included elements such as: the use of pedagogical model at UNA, the integration of TIC policies and participatory methodology. Finally, tests of qualitity were applied to this virtual course by a group of scholars interested in incorporating virtual worlds into their teaching and learning processes, which allowed to incorporate improvements to the course and by doing this it will be finished with the development of a quality product.